Comprehensive two-dimensional chromatographic techniques for ultra-trace quantitative analysis of chlorinated dioxins in South Africa - Rohwer, Egmont Richard (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2015.